Label-free and "signal-on" homogeneous photoelectrochemical cytosensing strategy for ultrasensitive cancer cell detection. Issue 75 (20th August 2020) - Lu, Fangfang; Yang, Limin; Hou, Ting; Li, Feng
Abstract : A "signal-on" homogeneous photoelectrochemical cytosensing platform was constructed for ultrasensitive cancer cell detection based on a G-quadruplex-inserted long dsDNA structure. Abstract : We report a label-free and "signal-on" homogeneous photoelectrochemical cytosensing system for ultrasensitive detection of cancer cells, which is a truly homogeneous PEC cytosensing system without the photoactive material immobilization and target recognition probe modification, providing a new avenue in early and accurate cancer diagnosis and clinical analysis.